Detection of Essential Amino Acids & Oils from Leucas sp. A Medicinally Important Plants of Lamiaccae - S.K. Markandeya2 and A.N. Dharasurkar1, G.L. Pachkore1* (Recent Research in Science and Technology, 2010)
Detection of essential amino acids and oil, were carried on the medicinally important plants Leucas cephalotus and Leucas martinicensis. The Leucas martinicensis is useful in fever, bronchitis, paralysis and in expelling mosquito. The Leucas cephalotus an infusion is used as a bath for hysterical fits and for pain in joints. Leaves are consumed for their palatability and nutritional or medicinal values. Leaves are good source of protein containing essential oil and amino acids. Also serve as food and health supplement to local people. The present investigation Leucas cephalotus and Leucas martinicensis were belong to family Lamiaceae provide valuable information about the presence of essential amino acids and oil. Also give the stronger indication of potential medicinal and nutritive values to human welfare. <span style="line-height: 110%; font-family: ";Arial Narrow";,";sans-serif";; color: black; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">Keywords<span style="line-height: 110%; font-family: ";Arial Narrow";,";sans-serif";; color: black; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">: Essential oils, Amino acid, Leucas sp., Lamiaceae